Safavid and Mughal Empires in Contact: Intellectual and Religious Exchanges between Iran and India in the Early Modern Era - Pourjavady, Reza; Rezania, Kianoosh (Entangled Religions, 2023)
In the introduction to this special issue, the editors attempt to portray the emergence/formation of a pluralistic atmosphere in Mughal India in the early modern era as a reciprocate reaction beginning with the migration of a group of not entirely religiously open-minded Iranian scholars to a not yet pluralistic Mughal India. They point out that the migration of Iranian scholars to Mughal India both enhanced the plurality of the Mughal intellectual atmosphere and their own openness. They then highlight some significant characteristics of the new/newly emerged discourse in the Mughal empire, such as pluralism, rationalism, antiquarianism, and Persianization. The editors moreover endeavor to point out these characteristics in the processes investigated by the authors of the special issue.